Photoinitiated free radical polymerization of methylmethacrylate by using of quinoxalines in the presence of aldehydes - Aydin, Meral; Arsu, Nergis (ELSEVIER SCIENCE SA, 2006)
A series of quinoxalines at different concentrations were used in the presence of benzaldehyde (BA) and phthaldialdehyde (PDA) to initiate the polymerization of methylmethacrylate (MMA) formulation containing 2-ethyl-2-(hydroxymethyl)-1,3-propanediol-trimethylmethacrylate (TMPTMA) as a multifunctional acrylate. Highest conversion percentage of polymerization of MMA were obtained in the presence of benzaldehyde when diphenylquinoxaline, phenanthroquinoxaline and acenaphthoquinoxaline were used as an initiator. In the case of benzaldehyde, benzoyl radical were possibly responsible for the initiation of polymerization where quinoxalines do not initiate polymerization of acrylates in the presence of oxygen. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: photopolymerization; free radical polymerization; quinoxaline; RT-FTIR; DECARBOXYLATION; Chemistry; Materials Science